Efficacy of Chlorhexidine and Irsha (Anti-plaque) Mouth-rinses on Reducing Dental Plaques - V Esfahanian; M Ketabi; Ara H Farman (مجله دانشکده دندانپزشکی اصفهان, 2007)
Introduction: Gingivitis is the most common type of gum disease, mainly caused by microbial plaque. Therefore, the plaque control plays an important role in preventing the incidence of gingivitis and other periodontal diseases. There are various methods to control dental plaque and chemical and mechanical methods are very common. The most common chemical method of plaque control is using mouth-rinses. This study compared the effects of two mouth-rinses on reducing dental plaque: Irsha which is an Iranian mouth-rinse product; and chlorhexidine which is a standard mouth-rinse.Methods and Materials: In this cross-over clinical trial study, 14 volunteers in two groups (n=7) participated. One group started with rinsing twice a day with 10 cc of chlorhexidine for a week, followed by 10 days stop and then a week of rinsing with Irsha (anti plaque). The other group followed the same procedure except that started with Irsha (anti plaque) mouth-rinse. The subjects refrained from all mechanical oral hygiene procedures during the weeks of using mount-rinses. The subjects were examined twice during the study and the Sillnes-Loe Plaque Indices were recorded before and after mouthwash periods. Data were analyzed using paired t-test to compare the mean of plaque indices before and after using each mouth-rinse and t-test to compare the mean of plaque reduction in the two groups.Results: The results showed that the mean plaque index was significantly reduced after using chlorhexidine, but Irsha had no significant plaque reduction (p=0.917).Conclusion: In brief, the results showed that while chlorhexidine is very effective in controlling dental plaque, the anti-plaque effects of Irsha is not considerable at all.Key words: Chlorhexidine, Irsha, Mouth-rinse, Anti plaque effect